Indigenous Development and the Cultural Captivity of Entrepreneurship - Peredo, Ana María; McLean, Murdith (Business & Society, 2013)
This article argues that thinking about entrepreneurship as a potential instrument for relief from endemic poverty and disadvantage, especially among the Indigenous, has all too often been captive to a concept of entrepreneurship that is built out of constrained economic and cultural assumptions. The authors develop this argument from a critical discussion of contributions by Karl Polanyi and Robert Heilbroner. The result is that approaches to venture have been encouraged that are sometimes a poor fit for the circumstances of those they are meant to benefit, and other forms that could have considerable promise have gone unexplored. This article outlines some features of Indigenous culture and build on the analysis of David Harper to construct an improved notion of entrepreneurship that allows for these distinctive features. The article concludes that research and policy making concerning entrepreneurship as an instrument of development among the Indigenous need to be undertaken with this reconstructed understanding of entrepreneurship that is a better fit for the realities of Indigenous culture.
Environmental Studies; Business Studies
Keywords: HEILBRONER; Robert; Indigenous development; Indigenous peoples; POLANYI; Karl; 1886-1964; cultural diversity; entrepreneurship; entrepreneurship and culture; poverty

The political economy of public sector trade union militancy under Keynesianism: The case of local government - Gill-McLure, Whyeda (Capital & Class, 2013)
Public service labour’s distinctiveness is insufficiently understood or recognised; and in its ad hoc growth under liberal ideologies of state intervention (those of Mill and Keynes), it has been treated both as if it were and were not public service labour. This paper teases out some of the crucial links between liberal ideologies of state intervention and the social praxis of public service unionism, outlining the latter’s historical struggle against this paradoxical treatment, which culminated in 1970s militancy. The paper supports this argument with a Marxist analysis of public sector labour, drawing on Polanyi’s ‘double-movement’ to understand the limitations of liberal ideologies of state intervention.
Business; Public Administration
Keywords: Marxist analysis; civil service; distinctiveness of public service labour; double movement; ideology; labor process; labour process; liberalism; political economy; public sector union militancy

Union Campaigns as Countermovements: Mobilizing Immigrant Workers in France and the United Kingdom - Tapia, Maite; Turner, Lowell (British Journal of Industrial Relations, 2013)
In this article, we compare recent innovative union campaigns: the ‘sans papiers’ campaign in France and the ‘Justice for Cleaners’ campaign in the United Kingdom, both based on a sustained grass-roots mobilization of immigrant workers. Rather than focusing on the ‘usual suspect’ explanatory factors, such as contrasting national settings, union power structures or traditions, our cross-national comparison highlights important underlying similarities in unions' strategic responses to a growing precarious immigrant workforce. In the absence of established channels of representation, both unions decided to act like social movements fighting for social protection. Using Polanyi's framework, we view both case studies as examples of countermovements against heightened levels of global liberalization and precarious employment.
Business; Industrial Relations; Labour Studies
Keywords: comparative labour; countermovement; human resources; international labour; unions